Metacare: A Cross-Platform Healthcare Management System Using Progressive UI Framework and MySQL - Hans Pper C. Cabigting; Mc Bryan C. Amen; Mark Jimson A. Lico; John Micole A. Marcelo; Cris Norman P. Olipas; Andrew Caezar A. Villegas; Ruth G. Luciano (Formosa Journal of Computer and Information Science, 2023)
The study aimed to design an automated system for a healthcare centre to manage their records. It aimed to describe the process of designing and developing the system using the modified waterfall model. The International Organization for Standardization (ISO) 25010 software standards were utilized to assess the technical feature of the system and the quality of using the system. The developmental research design was used, and IT experts and healthcare workers/residents served as the respondents. The results were analysed using weighted mean and frequency distribution, revealing that the system was successfully designed and developed using the software development model. IT experts and end-users evaluated the system with highly acceptable ratings. This study concluded that the system met the software quality standards assessment and recommended its implementation to benefit more people in the locality with further improvements